Estimating The Hydraulic Conductivity and Depositional Environment of Quaternary Deposits in Parts of Eastern Dahomey Basin - Richard Omotoso Fakolade (Teknik Geologi, Fakultas Teknik, Universitas Sriwijaya, 2023)
The use of empirical formulae has been widely adopted to quickly and modestly determine the hydraulic conductivity of soils. Research shows that several methods have been adopted using dimensional analysis and experimental measurements to determine hydraulic conductivity since the end of 19th Century, despite that, these have not been applied to the Holocene sediments in the coastlines of Ondo state. This research is aimed at estimating the hydraulic conductivity, transmisitivity and investigates the Palaeo-Environmental characteristics of the Quaternary deposits in parts of the eastern Dahomey basin, Nigeria via grain size characterization and approximation. The result of the grain size analysis indicated that the mean values vary from 0.84ɸ to 2.02ɸ with an average of 1.85ɸ, coupled with the standard deviation (0.48 to 1.09; av. 0.75ɸ), skewness (-8.74 - 0.267; av. 0.035) and kurtoses (0.95 - 2.21; av. 1.01) respectively. The hydraulic conductivity (m/s) results range from 0.17 to 1.75 with the mean value of 2.02, while that of transmisitivity (M2/s) ranges between 4.8 x 10-1 - 5.3x10-1 with the mean value of 5.3x10-1 respectively, indicating prevalence of aquifer of good performance. The aquiferous units are predominantly unconfined, with variable thickness and depth of occurrence. Multivariate discriminate functions revealed that Ilaje quaternary deposit may have been deposited dominantly in beach environment of shallow agitated water.